Study on designing an automated system of efficient HVAC control for energy saving in industrial buildings - Popa, V; Popa, L (IOP conference series. Materials Science and Engineering, 2018)
The article is focused on energy efficiency in industrial building automation and control activities. Within industrial buildings, heating and air conditioning systems (HVAC) must be well controlled. The main purpose of our work is to study and design an automated system of efficient HVAC control for energy saving in industrial buildings. Within our research, we have sought to obtain the optimal configuration of the automation network in the SIMATIC S7 programming environment, to realize the automation program, to define the graphical interface with the operator and to realize the configuration of the platform by the process simulation method. The relationship between building and the building's internal technical system consists of the HVAC system of the building, a system consisting of a series of interior installations, namely the building heating installation; the hot water production installation; the building's ventilation system; the building's cooling system. In order to achieve the indisputable level of quality, reliability and efficiency of HVAC equipment, equipments should be considered in their global environment. This means that in addition to the safe operation of equipments and the provision of efficient operating conditions, acoustic performance, energy savings, etc. will be considered. The increased energy efficiency occurs either when energy input is reduced for a given service level or services have been improved or increased for a given amount of energy input. Industrial buildings processes automation strategy is implemented through the Building Management System (BMS). The SCADA (Supervisory Control and Data Acquisition) network in industrial buildings provides an interconnection with the field elements at factory plant level. The SCADA command and control mode is based on the real-time data acquisition system in the process. These field elements, such as sensors, are monitoring in the SCADA network via a PC or a PLC (Programmable Logic Controller). The main results of our research are as following: automation of PLC & HMI processes; determining customer requirements; automation of PLC & HMI(Human Machine Interface) processes; determining customer requirements; realizing the system configuration for the automation process; realization of the process simulation platform architecture with SIMATIC S7-300 automatic programmable equipment. The most important consequence of the paper is the realization of a HVAC automation panel placed in a 4-level industrial hall.